2018
DOI: 10.1002/jmv.25231
|View full text |Cite
|
Sign up to set email alerts
|

HTLV‐1 and ‐2 in a first‐time blood donor population in Northeastern Brazil: Prevalence, molecular characterization, and evidence of intrafamilial transmission

Abstract: Independent epidemiology for respective human T-cell lymphotropic virus (HTLV) types 1 and 2 is little known in blood donors in Brazil, where screening for HTLV-1/2 is mandatory at blood banks, but no testing to confirm/differentiate these viruses. Therefore, this study aims to assess the prevalence of HTLV-1 and -2 in a first-time blood donor population in Northeastern Brazil and to carry out molecular characterization of respective isolates. A cross-sectional study was conducted at the State Blood Bank in Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…The investigation of HTLV-1/2 infections among FSWs is the first approach in Amazon Region of Brazil, particularly in a highly endemic area of HTLV infection (Ishak et al, 2020). The present study observed a higher general seroprevalence of HTLV-1 than those reported in the population of men who have sex with men (0.7%) (Malta et al, 2010); candidates for blood donation in the Northeast of Brazil (1.2%) (Ribeiro et al, 2018), the Brazilian state of Amazonas (0.13%) (Morais et al, 2017) and in non-FSW women who had a similar socioeconomic profile, such as pregnant teenagers (0.6%) (Guerra et al, 2018) and women from Belém, Pará (1.4%) (Silva et al, 2018) and parturients (0.4%) of Salvador, Bahia (Vargas et al, 2020). However, the seroprevalence was much lower than the figure recorded among illicit drug users in the state of Pará (6.4%) (Oliveira-Filho et al, 2019b).…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…The investigation of HTLV-1/2 infections among FSWs is the first approach in Amazon Region of Brazil, particularly in a highly endemic area of HTLV infection (Ishak et al, 2020). The present study observed a higher general seroprevalence of HTLV-1 than those reported in the population of men who have sex with men (0.7%) (Malta et al, 2010); candidates for blood donation in the Northeast of Brazil (1.2%) (Ribeiro et al, 2018), the Brazilian state of Amazonas (0.13%) (Morais et al, 2017) and in non-FSW women who had a similar socioeconomic profile, such as pregnant teenagers (0.6%) (Guerra et al, 2018) and women from Belém, Pará (1.4%) (Silva et al, 2018) and parturients (0.4%) of Salvador, Bahia (Vargas et al, 2020). However, the seroprevalence was much lower than the figure recorded among illicit drug users in the state of Pará (6.4%) (Oliveira-Filho et al, 2019b).…”
Section: Discussionsupporting
confidence: 42%
“…HTLV-1, but not HTLV-2, was identified among FSWs in three cities of the state of Pará, suggesting greater spread of the virus, although the prevalence was lower than HIV-1. Cosmopolitan subtype, Transcontinental subgroup, is the major subtype in circulation in the State of Para (Laurentino et al, 2005;de Aguiar et al, 2017;Ishak et al, 2020) and in other Brazilian regions (Nunes et al, 2017;Ribeiro et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have addressed HTLV prevalence in Brazil and Argentina revealing regions of high endemicity. In the former, the highest prevalence was demonstrated in the North-North East region, in particular in Salvador de Bahia, ranging from 0.046% to 1.8% [ 303 , 306 , 308 , 309 , 310 , 312 , 313 , 319 , 320 , 356 , 357 , 358 , 359 , 360 , 361 , 362 , 363 , 364 , 365 , 366 ], with slightly higher prevalence in specific villages with African characteristics, such as Piaui (2.24%) [ 359 ], Taquarendi (3.85%), Junco (1.23%), Alegre (1.56%) [ 363 ] and Marajó Island (1–2.06%) [ 366 ]. In the South and South Eastern regions, HTLV prevalence ranged from 0.02% to 1.5% [ 302 , 303 , 305 , 318 , 321 , 322 , 358 , 367 , 368 , 369 , 370 ].…”
Section: Human T-cell Lymphotropic Virusmentioning
confidence: 99%
“…In the South and South Eastern regions, HTLV prevalence ranged from 0.02% to 1.5% [ 302 , 303 , 305 , 318 , 321 , 322 , 358 , 367 , 368 , 369 , 370 ]. In urban Northern and Southern regions HTLV-1 prevailed over HTLV-2 [ 309 , 310 , 313 , 314 , 317 , 358 ]. The central region exhibited HTLV prevalence ranging from 0.02% to 1.6% [ 305 , 307 , 315 , 316 , 317 , 371 , 372 , 373 , 374 ], of which, for the Amazonian region, prevalence increased when indigenous villages were analyzed: 0.4–1.18% HTLV positivity in the city [ 375 , 376 , 377 , 378 ], whereas, in certain villages, the prevalence increased up to 13.88% [ 376 , 379 , 380 , 381 , 382 , 383 ].…”
Section: Human T-cell Lymphotropic Virusmentioning
confidence: 99%
“…Molecular studies based on the long terminal repeat (LTR) region have classified HTLV-1 in seven genetic subtypes (1a-1g) and HTLV-2 in four subtypes (2a-2d) (Vandamme et al, 1998;Gessain and Cassar, 2012). The HTLV-1a or Cosmopolitan subtype is the most prevalent worldwide (Gessain and Cassar, 2012), as well as in Brazil (Castro et al, 2018;Ribeiro et al, 2018) and in Pará state (Vallinoto et al, 2006;Nobre et al, 2018). The prevalence of HTLV coinfecting people living with HIV/AIDS (PLWHA) varies according to the studied population and the geographical region.…”
mentioning
confidence: 99%